2013
DOI: 10.1083/jcb.201207115
|View full text |Cite
|
Sign up to set email alerts
|

A novel pathway spatiotemporally activates Rac1 and redox signaling in response to fluid shear stress

Abstract: The GEF Tiam1 acts as a novel molecular link to the VE-cadherin–p67phox–Par3 polarity complex, leading to localized activation of Rac1 and NADPH oxidase in response to fluid flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 45 publications
5
72
0
Order By: Relevance
“…This idea also fits well with the observation that onset of unidirectional laminar shear initially activates the inflammatory pathways, but these pathways are downregulated at later times as cells align and the antiinflammatory pathways become dominant (55). The mechanistic basis for these effects is unknown, but a tantalizing clue comes from the finding that production of ROS by the NADPH oxidase complex in response to flow requires association of VE-cadherin with the oxidase complex through the polarity protein PAR3 (56). A link between alignment and atherosclerosis in vivo is supported by studies on syndecan4 -/-mice, in which ECs fail to align in flow; on a hypercholesterolemic background, these mice show increased atherosclerosis, including lesions in regions of laminar flow that are normally protected (57).…”
Section: Plaque Progression and Remodelingsupporting
confidence: 69%
“…This idea also fits well with the observation that onset of unidirectional laminar shear initially activates the inflammatory pathways, but these pathways are downregulated at later times as cells align and the antiinflammatory pathways become dominant (55). The mechanistic basis for these effects is unknown, but a tantalizing clue comes from the finding that production of ROS by the NADPH oxidase complex in response to flow requires association of VE-cadherin with the oxidase complex through the polarity protein PAR3 (56). A link between alignment and atherosclerosis in vivo is supported by studies on syndecan4 -/-mice, in which ECs fail to align in flow; on a hypercholesterolemic background, these mice show increased atherosclerosis, including lesions in regions of laminar flow that are normally protected (57).…”
Section: Plaque Progression and Remodelingsupporting
confidence: 69%
“…Flow induces TIAM1 association with VE-cadherin and the Par3-Par6-aPKC polarity complex at the downstream edge of the cell. Surprisingly, this role for TIAM1 does not require GEF activity but is required for coupling of Rac1 with its effector, the NADPH oxidase complex and production of reactive oxygen (Liu et al, 2013). These data point toward a highly intricate polarization mechanism involving a non-canonical function for TIAM1 in conjunction with membrane receptors and polarity proteins.…”
Section: Mechanosensors Of Endothelial Shear Stressmentioning
confidence: 94%
“…Interestingly, Rac1 activation is polarized toward the downstream edge of the cell relative to the flow direction, which mediates endothelial cell alignment. Recent work, however, showed that Rac1 activation by flow requires PECAM-1, acting through the Rac GEF VAV2; however, its spatial polarization requires a distinct GEF, TIAM1 (Liu et al, 2013). Flow induces TIAM1 association with VE-cadherin and the Par3-Par6-aPKC polarity complex at the downstream edge of the cell.…”
Section: Mechanosensors Of Endothelial Shear Stressmentioning
confidence: 99%
“…25 NF-κB activation in response to acute flow is also dependent on degradation of IκB by Rac GTPase-induced reactive oxygen species (ROS). 26 Therefore, both ROS and focal adhesion kinase signaling events are essential for nuclear translocation and transcriptional activity of NF-κB in response to acute flow. Although it has been shown that the content of extracellular matrix differs between atheroprone (fibronectin-rich) 27 and atheroprotected (collagen-rich) regions, 28 disturbed flow in combination with intergrin-fibronectin interaction is required for sustained NF-κB and JNK activation.. 29,30 Furthermore, a signaling pathway involving the adaptor protein Shc has been suggested as the molecular switch that coordinates interaction between cell-cell and cell-extracellular matrix, resulting in the initial extracellular matrix-independent activation of extracellular-signal-regulated kinase (ERK) on acute onset of flow to follow by extracellular matrix-dependent NF-κB activation.…”
Section: Signaling To Nf-κbmentioning
confidence: 99%